EFFECT PRODUCT, PRICES, PLACES AND PROMOTION ON THE DECISION TO BUY HYDROPONIC VEGETABLES ONLINE AT PT. SAYURAN PAGI DURING THE COVID-19 - Elpawati Elpawati; Iwan Aminudin; Nabila Rahmandika (Syarif Hidayatullah State Islamic University Jakarta, 2023)
The emergence of the COVID-19 pandemic has caused a change in behavior in society. Healthy and nutritious food such as hydroponic vegetables can be the right choice to consume during a pandemic. This is a good opportunity for hydroponic businesses such as PT. Sayuran Pagi, but until now its sales are known to be still volatile and tend to decline. This research aims to analyze online purchasing decisions during the pandemic which are influenced by variables of product, price, place and promotion on hydroponic vegetables products from PT. Sayuran Pagi both simultaneously and partially, as well as knowing which variables have the dominant effect. The sampling techniques used are descriptive analysis and multiple linear regression analysis. The results showed that a calculated F of 66,901 was obtained with a significance of 0.000. F table known with alpha 5% of 2,467. The results of calculation show that F calculates > F table (66,901 > 2,467) with a significance of < alpha (0.000 < 0.005). this means that the variables Product, Price, Place and Promotion have a significant effect together (simultaneously) on purchasing decisions. Meanwhile, based on the t test, it is known that the Promotion variable does not have a partial significant influence on the decision to buy hydroponic vegetables online at PT. Sayuran Pagi during the pandemic.